Engaging and transforming global communication through cultural discourse analysis a tribute to Donal Carbaugh - Scollo, Michelle; Milburn, Trudy; Carbaugh, Donal A. (Fairleigh Dickinson University Press series in communication studies., 2019)
"Global communication can be difficult in the best of circumstances. The contributors in this book take seriously the premise that one can examine communication within specific global settings and scenes with the goal of ensuring that the meanings made among those within specific communities is more clearly understood. This includes recognizing that we often communicate based on specific assumptions and act in ways that have normative bases that are shared with those within communities, but are often difficult to discern or navigate by those who are not members of them. Situated within the Ethnography of Communication research program, the contributors in this volume use Cultural Discourse Analysis to examine such practices, a theory and methodology developed by Donal Carbaugh over the past thirty years. The book is a celebration of his work and career, in which forty-four prominent Communication scholars and practitioners come together to use this framework to examine pressing communication issues across the globe. The book includes a preface by Gerry Philipsen that is an academic history of Carbaugh's career, an introduction outlining the history and current practice of Cultural Discourse Analysis, sixteen data based chapters using the framework to examine a broad range of inter/cultural communication practices across the globe, and an epilogue by Carbaugh reviewing this research and its future trajectory. The book is a handbook of Cultural Discourse Analysis for examining the latest in Cultural Discourse Analysis research and learning how to do such work that will be useful to advanced undergraduate and graduate students in a broad range of fields, inter/cultural communication scholars, and all those who seek to better understand and communicate in the global world today."